Contextual information needs of people in life transitions struggling with obsessive-compulsive disorder - Dawei Wu; Yuxiang Chris Zhao; Yan Zhang; Shijie Song (Information Research: An International Electronic Journal)
Introduction. Obsessive-compulsive Disorder (OCD) is a severe chronic mental health issue that significantly impacts people’s everyday lives. This study aims to reveal the contextual information needs of the people living with OCD during life transitions and how these needs dynamically evolve across various transitional stages.